1.
(2, 3) (1, 5)
Correct Answer
B. -2
Explanation
The given answer of -2 is obtained by subtracting the second coordinate (3) from the first coordinate (2). Therefore, 2 - 3 = -1. However, since the second coordinate (5) is greater than the first coordinate (1), the result is negated, resulting in -(-1) = -1. Thus, the correct answer is -1.
2.
(-6, 1) (2, 1)
Correct Answer
A. 0
Explanation
The answer is 0 because the y-coordinate of both points (-6, 1) and (2, 1) is the same. Therefore, the slope between the two points is 0, indicating that the line connecting them is horizontal.
3.
(3, 0) (5, 0)
Correct Answer
C. 0
Explanation
The given answer is 0. This is because the points (3, 0) and (5, 0) lie on the same horizontal line, which means the slope of the line passing through these points is 0. The slope of a line represents the change in y-coordinates divided by the change in x-coordinates between two points. Since the y-coordinates of both points are the same, the change in y-coordinates is 0. Therefore, the slope is 0, which is the correct answer.
4.
(5, 3) (5, -2)
Correct Answer
D. Undefined
Explanation
The given points (5, 3) and (5, -2) have the same x-coordinate, which means they lie on a vertical line. A vertical line has an undefined slope because the denominator of the slope formula becomes zero. Therefore, the slope between these two points is undefined.
5.
(3, -2) (7, -1)
Correct Answer
B. 1/4
Explanation
The given question provides two points, (3, -2) and (7, -1), and asks for the answer. To find the answer, we need to find the slope of the line passing through these two points. The slope is determined by the change in y-coordinates divided by the change in x-coordinates. In this case, the change in y is -1 - (-2) = 1, and the change in x is 7 - 3 = 4. Therefore, the slope is 1/4.
6.
Using the function, y = -5x, what would y equal if x were equal to 0?
Correct Answer
C. 0
Explanation
If x were equal to 0, the value of y would be determined by substituting x with 0 in the given function y = -5x. This would result in y = -5(0) = 0. Therefore, if x were equal to 0, y would also be equal to 0.
7.
Using the function, y = 3x + 1, what would y equal if x were equal to 2?
Correct Answer
D. 7
Explanation
If we substitute x=2 into the function y=3x+1, we get y=3(2)+1=7. Therefore, if x were equal to 2, y would equal 7.
8.
Using the function, y = -2x + 11, what would y equal if x were equal to 3?
Correct Answer
A. 5
Explanation
Substituting x = 3 into the given function, y = -2x + 11, we get y = -2(3) + 11 = -6 + 11 = 5. Therefore, if x were equal to 3, y would equal 5.
9.
Using the function, y = 7x - 3, what would y equal if x were equal to 4?
Correct Answer
B. 25
Explanation
If we substitute x = 4 into the equation y = 7x - 3, we get y = 7(4) - 3 = 28 - 3 = 25. Therefore, y would equal 25 if x were equal to 4.
10.
Using the function, y = -x, what would y equal if x equals -3?
Correct Answer
B. 3
Explanation
When using the function y = -x, we substitute x with -3 to find the value of y. Therefore, y = -(-3) = 3.